Effects of Milk Feeding Strategy and Acidification on Growth Performance, Metabolic Traits, Oxidative Stress, and Health of Holstein Calves - Gibson Maswayi Alugongo; Jianxin Xiao; Arash Azarfar; Shuai Liu; Mohammed Husien Yousif; Yulin Ma; Yangjing Wang; Shengli Li; Zhijun Cao (Frontiers in Animal Science, 2022)
Effects of milk feeding strategy and acidification on calf growth, metabolic traits, oxidative stress, and health were evaluated in the first 78 days of life. Holstein calves (N = 48; 12 calves/treatment) were assigned to 1 of the 4 treatments in a 2 × 2 factorial arrangement of milk feeding strategy [6 L/d (MOD) or 12 L/d (HIGH) of milk] and acidification [non-acidified milk (NAM) or acidified milk (ACM)] on day 2. Calves were bucket-fed milk as follows: 6 L/d from days 2 to 49 for MOD and 6 L/d from days 2 to 49, 12 L/d from days 7 to 42, and 8 L/d from days 43 to 49 for HIGH calves. All calves were then fed 4 L/d from days 50 to 56. Starter and water were available ad libitum, while hay was fed at 5% of starter from day 64. Calves were weighed, measured, and blood (except days 14, 42 and 56) sampled on days 2, 14, 28, 42, 49, 56, 63 and 78. Data were analyzed using Mixed PROC of SAS with time as repeated measurements. Fecal scores, checked daily, were examined by the logistic regression using a binomial distribution in GLIMMIX procedure. There were no three-way interactions observed for all the parameters. We detected a milk feeding strategy × time interaction for starter intake, body weight, ADG, ADG/ME, FE, structural measurements, and glucose. Although, overall (558.0 vs. 638.6 g/d), HIGH calves tended to consume less starter compared to MOD, significant differences were only observed in week 8. The HIGH calves had greater ADG during days 2–14 (1.12 vs. 0.75 kg/d) and tended to have greater ADG on days 15–28 (0.79 vs. 0.55) and 29–42 (0.86 vs. 0.60) and lower on days 57–63 (0.11 vs. 0.38) compared to MOD calves. The HIGH calves had greater BW from days 28 to 78 compared to MOD, while NAM were bigger compared to ACM calves from days 49 to 78. The HIGH calves had lower overall feed and metabolizable energy efficiencies compared to MOD. Except for BW and heart girth, no milk acidification × time interaction was observed for starter intake, ADG, FE, or ADG/ME. Blood glucose in calves fed NAM-HIGH and ACM-HIGH were greater compared to those fed moderate milk volumes on day 28 only. Albeit, feeding strategy had no effect, calves fed ACM had lower likelihood of experiencing diarrhea (odds ratio = 1.32; 95% confidence interval: 1.018–1.698) compared to those fed NAM. Overall milk feeding strategy had no effect on growth, while milk acidification reduced growth in calves, despite lowering the likelihood of experiencing diarrhea.